Assessment of cultural-technical condition of plants in pastures of Kayrakta rural district of Aitekebi district of Aktobe region (Eurasian Journal of Ecology, 2019)
This article provides a systematic list of plants, geobotanical characteristics, cultural and technicalcondition, economic values and forage reserves of pastures in the Kayrakta rural district of Aitekebidistrict of Aktobe region. In addition, the geographical location of the study area, topography, waterresources, climate and soil cover were fully studied and analyzed. The total number of pastures isdetermined by districts, and their classification and contours are shown on plant associations. Thestudy revealed 30 types of plant associations, 12 subtypes and 13 modifications. Types are dividedinto 16 groups, each of which is described individually.Detailed information was obtained on the seasonal use of pastures and the events held there, thetotal feed stock and its consumption in agriculture. As a result, 88 species from 24 plant families wererecorded in the area, 22 of which are eaten by livestock. Among them are eaten or poorly eaten, as well as toxic and medicinal plants. In order to reduce degraded pastures, recommendations were madeto improve livestock grazing on 1,030 hectares, reduce pastures on 4,970 hectares and fight weeds on93 hectares. Based on the results obtained, maps of the study area were mapped and indicators wererecorded.Key words: pastures, topography, water resources, soil cover, climate, plant associations, feedstock, livestock grazing, medicinal plants.